Integrating Leadership Strategies with Religious Values for Effective Educational Management in Multicultural Institutions - Sokip; Asrop Syafi'i; Nur ‘Azah; Zainur Arifin; Muh Ibnu Sholeh; Dinar Ayu Tasya (International Journal of Education Management and Religion, 2024)
This research discusses the integration of leadership strategies with religious values in educational management, particularly within multicultural educational institutions. The aim of this study is to identify how the implementation of religious values in leadership can enhance the quality of education, promote harmonious relationships among community members, and overall institutional success. Through a literature review approach, the study examines various literature related to religious-based leadership, including principles of justice, integrity, and care, as well as the challenges and successes of such integration. The results indicate that leaders who integrate religious values into their leadership strategies can create a more inclusive, harmonious, and productive educational environment. Additionally, the success of this integration can be seen in improved educational quality, higher satisfaction among students and staff, and increased community participation in school activities. However, challenges such as differences in religious values and resistance to change remain obstacles that must be addressed through interfaith and intercultural dialogue. This research concludes that the integration of religious values in educational management not only enhances the effectiveness of educational organizations but also strengthens social relations within the school community, providing a significant contribution to institutional success over the long term